2013
DOI: 10.1016/j.ajpath.2013.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Podocytes to Palmitic Acid Is Regulated by Stearoyl-CoA Desaturases 1 and 2

Abstract: Type 2 diabetes mellitus is characterized by dyslipidemia with elevated free fatty acids (FFAs). Loss of podocytes is a hallmark of diabetic nephropathy, and podocytes are highly susceptible to saturated FFAs but not to protective, monounsaturated FFAs. We report that patients with diabetic nephropathy develop alterations in glomerular gene expression of enzymes involved in fatty acid metabolism, including induction of stearoyl-CoA desaturase (SCD)-1, which converts saturated to monounsaturated FFAs. By IHC of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 45 publications
1
41
1
Order By: Relevance
“…In addition to intra-renal lipolysis, this study demonstrated, for the first time, that intra-renal desaturation of SFAs by SCD1 is also a therapeutic target for the prevention of PTEC damage in diabetic nephropathy. Furthermore, a previous report has shown that SCD1 activation has a cell-protective role in glomerular epithelial cells [30]. Given that SFA-mediated cellular toxicity contributes to both tubulointerstitial lesions and podocyte injury, stimulating SCD1 activity may become a novel therapeutic target for improving the renal prognosis by both reducing proteinuria and ameliorating PTEC damage in the refractory diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to intra-renal lipolysis, this study demonstrated, for the first time, that intra-renal desaturation of SFAs by SCD1 is also a therapeutic target for the prevention of PTEC damage in diabetic nephropathy. Furthermore, a previous report has shown that SCD1 activation has a cell-protective role in glomerular epithelial cells [30]. Given that SFA-mediated cellular toxicity contributes to both tubulointerstitial lesions and podocyte injury, stimulating SCD1 activity may become a novel therapeutic target for improving the renal prognosis by both reducing proteinuria and ameliorating PTEC damage in the refractory diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…124 Both endoplasmic reticulum stress and podocyte cell death could be ameliorated by inducing stearoyl-CoA desaturase 1, which converts saturated FFAs to monounsaturated FFAs and is upregulated in podocytes in biopsy samples from patients with DKD (Figure 2). 125 …”
Section: Cholesterol Free Fatty Acids and Dkdmentioning
confidence: 99%
“…Wilson et al () concluded that the depression of SCD1 gene expression as the result and not the cause of the diabetic state. Palmitic acid‐induced podocyte death was protected by pharmacologically stimulated SCD1 expression (Sieber et al, ; Sieber and Jehle, ); podocyte death in the kidney is critical in the pathogenesis of diabetic nephropathy. The very low level of SCD1 expression in the control SK6 suggests that this porcine kidney cell line does not reflect lipid metabolism in the kidney of whole animals.…”
Section: Discussionmentioning
confidence: 99%